Editorial - Abbas, Andrea (Critical Studies in Teaching and Learning, 2023)
Taken together, the five papers and one book review in Volume 10, Issue 2 of CriSTaL point to the need for broad sweeping, deep transformations on the part of universities who are currently driven by the priorities of a massified, marketised, performative, and usually under resourced global higher education system. The papers particularly draw out how new challenges arise within the context of more technology-based learning. In focusing on critical issues within specific university contexts, each paper in this journal identifies and unpacks an oppressive practice that is embedded within the South African system, but each paper also develops a degree of optimism, by identifying concepts and practices that do or could help us build towards greater social justice through higher education.